A Comparative Study of the Application of Swarm Intelligence in Kruppa-Based Camera Auto-Calibration - Jaafar, Hazriq Izzuan (2013)
This paper presented a comparative study of the application of two Swarm Intelligence algorithms: Particle Swarm Optimization and Firefly Algorithm in automatic camera calibration problem. The fitness function used in the camera calibration problem is based on the Kruppa’s equation. A case study from a dataset provided by Le2i Universite de Bourgoune is taken for benchmarking the performance of both algorithms. The result is compared with previous literatures. Result obtained from these algorithms indicates there is potential for further improvement.